ROYALISM, RELIGION AND REVOLUTION wales, 1640 -1688. - CLAVIER, SARAH WARD (Studies in early modern cultural, political and social history, 2021)
Analyses the role of long-term continuities in the political and religious culture of Wales from the eve of the Civil War in 1640 to the Glorious Revolution of 1688.